Current status of transvaginal mesh implants use in the surgical treatment of stress urinary incontinence and pelvic prolapse - Rustam A. Shakhaliev; Andrei S. Shulgin; Nikita D. Kubin; Irina N. Kuzmina; Denis A. Suchkov; Dmitry D. Shkarupa (IP Berlin A.V., 2022)
The use of synthetic implants in stress urinary incontinence and pelvic prolapse surgery is being actively debated today, not only among experts in the field but also in the media, the patient community, and even in legal and political set. Such response has had a natural effect on the clinical application of the technology. An absurd situation is observed in some countries: the bans imposed by the authorities have directly or indirectly restricted patients' access to the most sophisticated technologies with proven efficacy. This literature review aims to systematize the perspectives of the scientific and regulatory communities in leading countries on the use of transvaginal mesh implants in the treatment of stress urinary incontinence and pelvic prolapse.